Inclusion of Research Materials When Submitting an Article to Language Learning. Issue 4 (29th October 2019) - Marsden, Emma; Crossley, Scott; Ellis, Nick; Kormos, Judit; Morgan‐Short, Kara; Thierry, Guillaume
Abstract: Building on initiatives to promote high quality methodologies and Open Science practices in the language sciences, Language Learning will request, as of January 1, 2020, that all submissions to the journal include, whenever possible, the full materials used in the study for peer review. This includes materials used to elicit and code primary and secondary data (such as questionnaires, language tests, interview or observation schedules, and coding schemas). These materials will be shared with reviewers to better inform the peer review process and ensure rigorous evaluation of the methods used. If the manuscript is accepted, authors will then be encouraged to make their materials available on an open, sustainable repository, though there is no requirement to do so. In this Editorial, we outline the benefits of this policy for the advancement of the language sciences and discuss some potential concerns that authors may have.